Ten years of anti-dumping in the EU: Economic and political targeting - Lucy Davis (European Centre for International Political Economy (ECIPE), 2009)
Anti-dumping is at the heart of EU trade policy. Its use is justified on the grounds of eliminating injurious dumping by foreign firms and re-establishing conditions of "fair" trade. Use of anti-dumping has been rising globally, generating concerns about the potential for protectionist abuse of this trade defence instrument. Most economists are of the opinion that anti-dumping has little to do with "unfair" trade. In general, suspicions are high that domestic industries are turning to anti-dumping as a form of protectionism, and that the EU's current anti-dumping laws support their efforts. This paper takes an in-depth look at the past ten years of anti-dumping usage in the EU. The analysis draws on information from the 332 anti-dumping cases initiated between 1998 and 31 December 2008. Five empirical tendencies have been identified: The main targets of investigations and measures are exporters in emerging markets, particularly in 1. Asia - a growing source of global competition; Targeted products are concentrated in sectors where European comparative advantage is declining, 2. i.e. raw materials, industrial input goods and textiles; Dumping margins reflect this pattern, being particularly high in the chemicals and steel sectors; 3. Duty levels are significantly higher than bound tariffs, particularly in the higher-end technology 4. sector. Once an anti-dumping investigation has been initiated, definitive measures are the most likely 5. outcome.
Keywords: 330; Antidumping; EU-Recht; Protektionismus; EU-Staaten